Determination of Minimal Hemoglobin Level Necessary for Normothermic Porcine Ex Situ Liver Perfusion. Issue 8 (August 2018) - Bral, Mariusz; Gala-Lopez, Boris; Thiesen, Aducio; Hatami, Sanaz; Bigam, David L.; Freed, Darren M.; James Shapiro, A.M.
Abstract : Background: In current studies of ex situ liver perfusion there exists considerable variability in perfusate composition, including the type of oxygen carrier. Herein, we aim to clarify the minimal hemoglobin level necessary during normothermic porcine ex situ liver perfusion. Methods: Livers procured from 35 to 45 kg domestic pigs were connected to our experimental ex situ circuit (n = 10). In the treatment group, perfusate was sequentially diluted hourly to predetermined hemoglobin levels. At the end of each hemoglobin dilution, perfusate samples were analyzed for liver transaminases, lactate dehydrogenase (LD), total bilirubin, and lactate levels. Liver oxygen consumption was measured. In the control group, livers were perfused continually for a duration of 24 hours at target hemoglobin levels of 30 and 20 g/L. Results: Rising liver transaminases, significantly higher lactate ( P < 0.001), and LD levels ( P < 0.001) were noted at lower perfusate hemoglobin levels in the treatment group. Liver oxygen utilization ( P < 0.001) and hepatic artery oxygen delivery ( P < 0.001) were significantly lower at lower hemoglobin levels, whereas liver vessel resistance remained relatively constant. Histology demonstrated increasing parenchymal damage at lower hemoglobin levels. In control livers, higher perfusate transaminases, higher lactate, and LD levels were noted at a perfusion hemoglobin level of 20 g/L. Conclusions: Ex situ liver function decompensated during perfusion between a mean hemoglobin level of 30 to 20 g/L, as evidenced by notably rising lactate and LD levels. This study demonstrates optimal hemoglobin concentration during normothermic ex situ liver perfusion to ensure a fully metabolically functioning graft. Abstract : The authors demonstrate that hemoglobin concentration between 30-20 g/L should be maintained to assure optimal liver graft function under normothermic ex situ perfusion conditions in a porcine model.